Impairment of botrydial production in Botrytis cinerea allows the isolation of undescribed polyketides and reveals new insights into the botcinins biosynthetic pathway. (March 2021) - Moraga, Javier; Izquierdo-Bueno Reina, Inmaculada; Pinedo, Cristina; Hernández-Galán, Rosario; Viaud, Muriel; Collado, Isidro G.
Abstract: Botrytis cinerea is a necrotrophic fungal pathogen that affects a total of 586 genera representing approximately 1400 plant species. This pathogen produces two families of phytotoxins involved in its infection process i.e. botrydial and its relatives, and botcinic and botcineric acids and their relatives, botcinins. The botrydial biosynthetic cluster consists of seven genes, where the gene BcBOT4 encodes a cytochrome P450 monooxygenase that was shown to catalyse regio- and stereospecific hydroxylation at position C-4 of the presilphiperfolan-8-β-ol skeleton. The null mutant bcbot4Δ halted the production of botrydial and its derivatives, and instead accumulated tricyclic presilphiperfolane alcohol and overproduced a significant number of polyketides. A detailed study of the bcbot4Δ mutant led us to the isolation and characterization of five undescribed polyketides, three derived from botcinic and botcineric acids (botcinins H, I, J), one derived from the initial pentaketide (botcinin K), and one cinbotolide derivative (cinbotolide D). Botcinins are tetra-methylated tetraketides biosynthesized by the sequential assembly of a pentaketide (C10) based on an acetate primer unit which is lost through a retro-Claisen type C–C bond cleavage. The structural characterization of botcinin K showed a basic chemical structure corresponding to a botcinin (C14) derivative obtained directly from the original per-methylated pentaketide leading to the biosynthesis of botrylactone and other botcinins, confirming the previously proposed biosynthetic route. Graphical abstract: Image 1 Highlights: The null mutant bcbot4Δ overproduced a significant number of polyketides. Four botcinins and one cinbotolide were characterized from null mutant bcbot4Δ . Isolation of botcinin K confirmed the biosynthetic pathway to botcinin derivatives.